Development of Invertebrate Module Based in PJBL for Class X - Herditiya, Herditiya; Ngabekti, Sri; Partaya, Partaya (Journal of Innovative Science Education, 2020)
The learning process in the classroom is currently still using sources from textbooks books that make students bored so that students learning interest is reduced and does not arouse students' curiosity in the learning process, the availability of learning support books is needed, one of them is by developing modules. Module specifications were developed based on the results of Invertebrate exploration. The purpose of this study is, (1) to explain the types of Invertebrates found to compile modules, (2) to find the characteristics of modules (3) to test the validity, practicality, and effectiveness of Invertebrate module based in PjBL. This research is an R & D conducted in SMA N 1 Sungai Raya, class X in the 2018/2019 school year. The results showed as many as 20 types of several Invertebrate phylum found on Lemukutan Island and Kakap Estuary Coast. The results of the module validation from the material experts 89.80 and 98.38 media experts with very valid criteria. The practicality results of students 86.46 with very practical criteria, and effectiveness seen from the cognitive results with classical completeness of 97%, and the psychomotor value of students amounted to 91.53 with very good criteria. The conclusion from this study is that the Invertebrate module in PjBL-based is valid, practical, and effective in the learning process.